Determinan Kemiskinan Anak di Provinsi DKI Jakarta: SUSENAS 2017 - Ramadhani, Aji Wahyu; Munandar, Adis Imam (Jurnal Ekonomi Kuantitatif Terapan; 2019: Vol. 12, No.2, Agustus 2019 (pp. 111-247)DO - 10.24843/JEKT.2019.v12.i02.p01, 2019)
Child poverty is a problem that often occurs in big cities. The child poverty rate (P0) in DKI Jakarta Province in March 2017 is 6.10%, which is equivalent to 182,212 people, with a poverty depth index (P1) of 0.7997 and a poverty severity index (P2) of 0.1609. The study aims to analyze the poverty determinants of children from household characteristics using SUSENAS 2017. Results of the method used are logistic regression analysis. The results of the study showed that household characteristics that significantly affected the poverty status of children were the education level of the head of the household, the working status of the mother, and the number of members in the household. One of the government's family planning programs needs to be increased to reduce child poverty in DKI Jakarta